Die ontwikkeling van inboorlingonderwys binne die suidelike sektor van Suidwes-Afrika, 1915-1962 - Scholtz, P. J.(Petrus Jurie) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Ed.) -- Universiteit van Stellenbosch, 1973.